1987
DOI: 10.1063/1.451980
|View full text |Cite
|
Sign up to set email alerts
|

High pressure isotropic bandwidths and frequency shifts of the C–H and C–O modes of liquid methanol

Abstract: The Raman bands of the C–H ν3 and C–O ν8 stretching modes of liquid methanol have been measured at temperatures ranging from 273 to 363 K and pressures from 10 bar to 4 kbar. The effects of density and temperature on the isotropic linewidth, peak frequency of the isotropic band, ν0 (ISO), and the difference δν between anisotropic ν0(VH) and ν0(ISO) band frequencies are reported and discussed qualitatively in terms of available theoretical models. It appears that repulsive interactions are responsible for the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 29 publications
3
59
0
1
Order By: Relevance
“…A number of other investigators [3][4][5] also observed this effect in liquids under pressure. The non-coincidence effect is the observation that the peak frequency for anisotropic Raman peak maximum, I aniso (x) (identified with depolarized band I VH (x)), is at a different position than that of isotropic Raman peak maximum, I iso (x).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…A number of other investigators [3][4][5] also observed this effect in liquids under pressure. The non-coincidence effect is the observation that the peak frequency for anisotropic Raman peak maximum, I aniso (x) (identified with depolarized band I VH (x)), is at a different position than that of isotropic Raman peak maximum, I iso (x).…”
Section: Introductionmentioning
confidence: 69%
“…were under a constant pressure and varying temperature or sometimes at constant density [2][3][4][7][8][9][10]. Typical spectra showing Raman scattering results from NBS-710 glass are given in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11r 11so· First observations of the non-coincidence effect [71] have shown that 11so < Vaniso• VfR, and hence ~ VNcE>O; such observation is peculiar to the vast majority of molecular liquids. The so-called "anomalous" or negative non-coincidences have first been reported for molecular liquids in 1987 [79], in this case 11so> Voniso, l1R, and~ VNce<O. It should be mentioned, however, that a similar effect for molten nitrates has been described by Brooker and Papatheodorou much earlier, in 1983 [89].…”
Section: Non-coincidence Effects Caused By Resonance Energy Transfermentioning
confidence: 77%
“…This means that anomalous non-coincidence effects may arise due to repulsion forces. Anomalous non-coincidence effects are actively pursued since the time of their discovery [79,80]; the latest reviews of the subject can be found in Refs [10][11][12][13][14][15][16][17]. However, repulsion forces have never been quantitatively taken into account in non-coincidence effect studies.…”
Section: Introductory Remarksmentioning
confidence: 99%
“…67 The calculated isotropic Raman spectra peak is located at 1060.0 cm −1 with a FWHM of 19.2 cm −1 , while the peak of anisotropic Raman spectra is located at 1051.1 cm −1 with a FWHM of 34.6 cm −1 , leading to a NCE of −8.9 cm −1 . The peak positions are larger than the experimental ones 6,28,29 by about 20 cm −1 , which should be due to the inaccuracy of the DFT calculation of the vibrational frequencies. The isotropic and anisotropic components of the Raman spectra of CO stretch of pure methanol liquid have been studied exper- imentally.…”
Section: ■ Theoretical Methodsmentioning
confidence: 85%